The Impact of Tourism Receipts on Economic Development: A Panel Data Analysis for Selected Asian Countries - Anis, Ammara; Khushbakhet, Maria; Maqbool, Muhammad Shahid (Pakistan Journal of Humanities and Social Sciences, 2023)
The current study aims at studying tourism which has emerged as one of the most dynamic rising international industries for economies. The present study inspects the influence of tourism receipts, trade openness, investment and population on the economic growth of selected Asian nations between 1995 and 2021. The data for the variable of interest has been taken from the Global Development Indicator (WDI). Checks for LLC and IPS have been conducted on stationary. Both the models, FMOLS and the Dynamic OLS, have been used to capture both short and long-run flexibility. For this objective, the Granger causality technique has been utilized. The results indicate that tourism receipts have a favorable and substantial effect on the economic growth of some Asian nations. The study also shows that the tourism sector has ample capacity to contribute to economic growth; therefore, tourist-attractive places should be provided with essential amenities such as connectivity and infrastructure.